Effectiveness of Group Guidance Services using Sociodrama Techniques to Improve Self-control of Students of State Senior High School 1 Karangnongko Klaten - Irfan Rusydi; Arum Setiowati (Ma'soem University, 2024)
The purpose of this research was to examine the impact of sociodrama techniques on students' self-control at SMA Negeri 1 Karangnongko Klaten. Utilizing a pre-experimental design, the study selected a purposive sample of 6 students from a total population of 125 students across four classes (grade X and XI). Data on self-control were collected via a questionnaire and analyzed using a Paired Sample t-test. The analysis revealed a statistically significant increase in self-control after the sociodrama intervention, as evidenced by a t-value of -4.945 and a significance level of 0.004 (p < 0.05). Consequently, the findings support the conclusion that sociodrama techniques are effective in enhancing students' self-control.